Nivolumab Plus Ipilimumab Versus EXTREME Regimen as First-Line Treatment for Recurrent/Metastatic Squamous Cell Carcinoma of the Head and Neck: The Final Results of CheckMate 651. Issue 12 (20th April 2023) - Haddad, Robert I.; Harrington, Kevin; Tahara, Makoto; Ferris, Robert L.; Gillison, Maura; Fayette, Jerome; Daste, Amaury; Koralewski, Piotr; Zurawski, Bogdan; Taberna, Miren; Saba, Nabil F.; Mak, Milena; et al.
Abstract : PURPOSE: CheckMate 651 (ClinicalTrials.gov identifier: NCT02741570 ) evaluated first-line nivolumab plus ipilimumab versus EXTREME (cetuximab plus cisplatin/carboplatin plus fluorouracil ≤ six cycles, then cetuximab maintenance) in recurrent/metastatic squamous cell carcinoma of the head and neck (R/M SCCHN). METHODS: Patients without prior systemic therapy for R/M SCCHN were randomly assigned 1:1 to nivolumab plus ipilimumab or EXTREME. Primary end points were overall survival (OS) in the all randomly assigned and programmed death-ligand 1 combined positive score (CPS) ≥ 20 populations. Secondary end points included OS in the programmed death-ligand 1 CPS ≥ 1 population, and progression-free survival, objective response rate, and duration of response in the all randomly assigned and CPS ≥ 20 populations. RESULTS: Among 947 patients randomly assigned, 38.3% had CPS ≥ 20. There were no statistically significant differences in OS with nivolumab plus ipilimumab versus EXTREME in the all randomly assigned (median: 13.9 v 13.5 months; hazard ratio [HR], 0.95; 97.9% CI, 0.80 to 1.13; P = .4951) and CPS ≥ 20 (median: 17.6 v 14.6 months; HR, 0.78; 97.51% CI, 0.59 to 1.03; P = .0469) populations. In patients with CPS ≥ 1, the median OS was 15.7 versus 13.2 months (HR, 0.82; 95% CI, 0.69 to 0.97). Among patients with CPS ≥ 20, the median progression-free survival was 5.4 months (nivolumab plus ipilimumab) versus 7.0 months (EXTREME), objective response rate was 34.1% versus 36.0%, and median duration of response was 32.6 versus 7.0 months. Grade 3/4 treatment-related adverse events occurred in 28.2% of patients treated with nivolumab plus ipilimumab versus 70.7% treated with EXTREME. CONCLUSION: CheckMate 651 did not meet its primary end points of OS in the all randomly assigned or CPS ≥ 20 populations. Nivolumab plus ipilimumab showed a favorable safety profile compared with EXTREME. There continues to be a need for new therapies in patients with R/M SCCHN.